Recovery of Silica from Steel Slag Waste Using Extraction and Acid Precipitation Methods - Betafachreza, Aditya Fadhilaskha; Putra, Boni Mulia; Pujiastuti, Caecilia (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Steelmaking processes generate large amounts of slag waste that contain silica, which can be recovered and converted into valuable products. In this study, silica (SiO?) was extracted from steel slag waste through alkaline extraction using sodium hydroxide (NaOH) followed by acid precipitation. The experimental parameters included NaOH concentrations of 0.5, 1.0, 1.5, 2.0, and 2.5 M, and extraction temperatures of 60, 70, 80, 90, and 100 °C. Each extraction was carried out for 60 minutes with continuous stirring at 300 rpm. The X-ray diffraction (XRD) analysis confirmed that the product exhibited a broad peak at 2? around 20–30°, which is characteristic of amorphous silica. The results indicated that both NaOH concentration and temperature had a positive correlation with silica yield. As the NaOH concentration and extraction temperature increased, the percentage of extracted silica also increased. The optimum condition was achieved at 100 °C and 2.5 M NaOH, yielding silica with a purity of 91.10%. These findings highlight the potential of utilising steel slag waste as a low-cost raw material for producing amorphous silica. Furthermore, the process demonstrates a sustainable approach to waste valorization while providing high-purity silica for potential applications in industrial materials, adsorbents, and nanotechnology. Contribution to Sustainable Development Goals (SDGs):SDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land